2017
DOI: 10.1038/s41467-017-01002-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective purifying selection in ancient asexual oribatid mites

Abstract: Sex is beneficial in the long term because it can prevent mutational meltdown through increased effectiveness of selection. This idea is supported by empirical evidence of deleterious mutation accumulation in species with a recent transition to asexuality. Here, we study the effectiveness of purifying selection in oribatid mites which have lost sex millions of years ago and diversified into different families and species while reproducing asexually. We compare the accumulation of deleterious nonsynonymous and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 75 publications
(67 reference statements)
1
45
2
Order By: Relevance
“…2016 ). Or very old (tens of millions of years) and accumulating deleterious mutations at lower rates than sexual species, opposite to theoretical predictions ( Brandt et al. 2017 ).…”
Section: Discussionmentioning
confidence: 76%
“…2016 ). Or very old (tens of millions of years) and accumulating deleterious mutations at lower rates than sexual species, opposite to theoretical predictions ( Brandt et al. 2017 ).…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, one of the four cases that did investigate mutation accumulation at the whole‐genome scale in the wild found that, contrary to predictions, sexual taxa experienced more mutation accumulation (Brandt et al. ). Finally, although there appears to be some tentative general support for deleterious mutation accumulation in asexual lineages, it is important to note that even broad support for this mechanism is unlikely to explain the maintenance of sex.…”
Section: Discussionmentioning
confidence: 93%
“…The fourth study (Brandt et al. ) found that sexual taxa experienced more mutation accumulation than asexual counterparts. This latter study focused on asexual lineages that are extremely old (tens of million years since derivation from sexual ancestors), suggesting that the absence of deleterious mutation accumulation may have contributed to the long‐term persistence of these lineages in the absence of sex.…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison of obligate sexual and asexual individuals in the freshwater snail Potamopyrgus antipodarum , three meiosis-specific genes ( spo11 , msh4 and msh5 ) exhibited no degeneration in the asexual lineages, but were instead inferred to be under purifying selection [ 79 ]. Also, for three ancient asexual oribatid mites, there is stronger purifying selection on nuclear and mitochondrial orthologous genes compared to sexual species [ 80 ]. For the microcrustacean Daphnia pulex, whose reproduction cycle consists of alternating sexual and asexual phases, the main meiosis genes are present in the genome and are expressed under parthenogenesis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%